An Analysis of the Effect of Utilitarian Values on Shopee E-Commerce Satisfaction and Loyalty with SEM-PLS - Valentika, Nina (Universitas Islam Negeri Raden Intan Lampung, 2020)
This research examines Shopee consumers who have shopped at least once and are students in the Department of Accounting, Faculty of Economics, Pamulang University. The method used was the Structural Equation Modeling-Partial Least Square (SEM-PLS). The purpose of this research was to examine the direct effect of utilitarian values on satisfaction, examine the direct effect of satisfaction on loyalty, and examine the indirect effect of utilitarian values on loyalty. Based on the results of the research, it can be concluded that there was a significant influence on satisfaction and loyalty, utilitarian values, and satisfaction, as well as utilitarian values and loyalty. There was a significant influence of Utilitarian values and loyalty with satisfaction as an intervening variable.